2004
DOI: 10.1002/zaac.200400115
|View full text |Cite
|
Sign up to set email alerts
|

3D Coordination Polymer Incorporating Discrete Molecular Octahedra

Abstract: Copper(II) oxalate coordination polymer [{Cu4(C2O4)4(L)4}3 · {Cu3(C2O4)3(L)6}2 · 3L · 25H2O]n (L = 3,3′,5,5′‐tetramethyl‐4,4′‐bipyrazole) reveals a structure that is related to the Pt3O4 net topology. The 3D linkage is sustained with copper‐oxalate squares and copper‐bipyrazole triangles sharing vertices. The framework supports giant icosahedral cages and entraps discrete molecular octahedra formed by two molecular complexes Cu3(C2O4)3(L)6 associated by means of NH‐‐‐N hydrogen bonding. The coexistence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In coordination compounds, Me 4 bpz normally appears as an exobidentate ligand, whereby the connected metal centers adopt distances between 9.0 and 10.5 A ˚. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The two not coordinated nitrogen atoms normally act as donor atoms in hydrogen bonds, which is a fundamental difference to the triazole-based ligand recently used in a study on mixed ligand systems with an aromatic tricarboxylate. 40 The flexibility of this ligand arises from the nearly unhindered torsion of the pyrazole rings along the single bond between the rings and can lead to very different coordination conformations (observed angles between the pseudoaromatic ring planes j are between 55 and 90°), where the more topological flexibility of the carboxylate ligands arises from the ability to realize different binding modes to the metal centers.…”
Section: Introductionmentioning
confidence: 99%
“…In coordination compounds, Me 4 bpz normally appears as an exobidentate ligand, whereby the connected metal centers adopt distances between 9.0 and 10.5 A ˚. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The two not coordinated nitrogen atoms normally act as donor atoms in hydrogen bonds, which is a fundamental difference to the triazole-based ligand recently used in a study on mixed ligand systems with an aromatic tricarboxylate. 40 The flexibility of this ligand arises from the nearly unhindered torsion of the pyrazole rings along the single bond between the rings and can lead to very different coordination conformations (observed angles between the pseudoaromatic ring planes j are between 55 and 90°), where the more topological flexibility of the carboxylate ligands arises from the ability to realize different binding modes to the metal centers.…”
Section: Introductionmentioning
confidence: 99%
“…We have been unable to find any references in the literature to any other compound containing a monoprotonated 3,3 0 ,5,5 0tetramethylbipyrazole ligand coordinated only to one metal atom through a single nitrogen donor, but Komarchuk et al (2004) reported a compound containing two unprotonated tetramethylbipyrazole ligands acting as ligands to a single copper atom. For an exploration of N-HÁ Á ÁCl interactions in the design and synthesis of crystal structures with desired properties such as unit-cell metrics or defined reactivity, see: Adams et al (2005).…”
Section: Related Literaturementioning
confidence: 93%
“…The crystal structures of these compounds were determined only recently. They include the cadmium (Boldog et al, 2001b;Boldog, Rusanov et al, 2003;, cobalt (Boldog et al, 2001a;Ponomarova et al, 2002), copper (Boldog et al, 2001b;He et al, 2006;Komarchuk et al, 2004;Kruger et al, 2000), nickel (Kruger et al, 1992;Ponomarova et al, 2002), palladium (Yu et al, 2005;Zhang et al, 2004), silver (Boldog et al, 2001b;Domasevitch et al, 2005) and tungsten (Tang et al, 2004) complexes. The 1:2 cobalt(II) dithionate adduct is a porous compound with 29% of its unitcell volume as voids; the Co atom is covalently bonded to the dithionate units in an octahedral geometry.…”
Section: Commentmentioning
confidence: 99%